Supply Chain Management Practices (SCMP) On Sentra Industri Tahu Cibuntu Bandung - Apriliya, Lidya Clarisah; Hutami, RR. Rieka F. (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: The purpose of this paper is to investigate the implementation of supply chain management practices (SCMP) on Sentra Industri Tahu Cibuntu Bandung.Methodology: This study utilizes survey data of 723 micro small and medium enterprises (MSME) Sentra Industri Tahu Cibuntu Bandung and sample size this study is 30 respondents. The methodology and hypothesis testing proposed in the conceptual in this research used descriptive. Results: This research suggests that the supply chain management practices (SCMP) effect on Sentra Industri Tahu Cibuntu Bandung.Applications/Originality/Value: This research is an attempt to empirically test the impact of supply chain management practices (SCMP) on Sentra Industri Tahu Cibuntu Bandung.